A Study on the Assessment of Body Awareness Ability in Normal Children: A Pilot Study - Ahn, Sinae (International Journal of Membrane Science and Technology, 2023)
Body awareness influences psychosocial development, and psychosocial factors are important in children’s developmental processes. This study assessed the potential impact of body awareness in healthy children. Children, their guardians, and assessors were asked to complete a questionnaire consisting of items on body awareness. The questionnaire included items on body awareness, including body and posture awareness, body sensitivity, body anxiety, and bodily feelings. The responses of the children, their guardians, and the assessors were analyzed. There was a difference in body awareness between the child and guardian but there was no statistical difference. There was a difference in response to body awareness between the child and assessors, but there was no statistical difference. This study presents evidence of body awareness in normal children. Future research using a group design should be conducted to confirm and generalize the results of this study.